The living treasures of Japan (1973)
This book which portrays some " living national treasures" the masters of traditional Japanese handicrafts and their works, from a new angle, was commissioned by mobil to describe the traditional crafts as they exist in modern Japan. As one of those consulted from the start of the project.
Keywords: Decorative arts,Handicraft,Artists; Japan; Japan,Japan